Alkaline modified biochar derived from spent coffee ground for removal of tetracycline from aqueous solutions. (April 2021) - Nguyen, Van-Truc; Nguyen, Thanh-Binh; Huang, C.P.; Chen, Chiu-Wen; Bui, Xuan-Thanh; Dong, Cheng-Di
Graphical abstract: Highlights: The NaOH-SCG exhibited better performance for TC removal than the SCG. The PAHs (693 μg kg −1 ) in NaOH-SCG was within permissible limits of IBI and EBC. The NaOH-SCG had high surface area (116.591 m 2 g −1 ) compared to SCG (3.644 m 2 g −1 ). The ionic strength significantly influenced the TC removal of the NaOH-SCG. The maximum monolayer adsorption capacity (qmax ) was 113.6 mg g −1 at pH 7 and 25 ℃. Abstract: The feasibility of applying alkaline modified-biochar prepared through pyrolysis of spent coffee ground (NaOH-SCG) in the elimination of tetracycline (TC) from different aqueous solutions was investigated through this study. The physico-chemical characterization of NaOH-SCG was scrutinized by distinct techniques. The PAHs concentration of NaOH-SCG (500 °C) was 693 μg kg −1, which do not exceed the international acceptable threshold of PAHs in biochar as reported by International Biochar Initiative (6–20 mg kg −1 ) and European Biochar Certificate (4 mg kg −1 for premium class, 6 mg kg −1 for basic class). From the experimental results, the adsorption capacity (qmax ) of NaOH-SCG biochar (113.64 mg g −1 ) exhibited 2.9 times higher than that of the non-modified SCG (39.22 mg g −1 ). Furthermore, environmental factors, namely, pH and ions, affecting the interaction between biochar and TC was investigated. Alkaline modified-biochar exhibited high tetracycline adsorption capacity and therefore has a great prospect as an environmentally effective adsorbent in separation of hazardous chemicals from different aqueous solutions.